2018 15th Conference on Computer and Robot Vision (CRV) 2018
DOI: 10.1109/crv.2018.00034
|View full text |Cite
|
Sign up to set email alerts
|

Robust UAV Visual Teach and Repeat Using Only Sparse Semantic Object Features

Abstract: We demonstrate the use of semantic object detections as robust features for Visual Teach and Repeat (VTR). Recent CNN-based object detectors are able to reliably detect objects of tens or hundreds of categories in video at frame rates. We show that such detections are repeatable enough to use as landmarks for VTR, without any low-level image features. Since object detections are highly invariant to lighting and surface appearance changes, our VTR can cope with global lighting changes and local movements of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Early work in mobile robotics has already shown that the ability to recognize trees from non-trees in combined LiDAR+camera sensing can improve localization robustness [1]. More recent work on data-efficient semantic localization and mapping algorithms [2], [3] have demonstrated the value of semantically-meaningful landmarks; In our situation, trees and the knowledge of their species would act as such semantic landmarks. The robotics community is also increasingly interested in flying drones in forests [4].…”
Section: Introductionmentioning
confidence: 89%
“…Early work in mobile robotics has already shown that the ability to recognize trees from non-trees in combined LiDAR+camera sensing can improve localization robustness [1]. More recent work on data-efficient semantic localization and mapping algorithms [2], [3] have demonstrated the value of semantically-meaningful landmarks; In our situation, trees and the knowledge of their species would act as such semantic landmarks. The robotics community is also increasingly interested in flying drones in forests [4].…”
Section: Introductionmentioning
confidence: 89%
“…Graph matching based on random walk [30] is a robust graph matching algorithm for outliers and deformations.…”
Section: Graph Matching Problem Formulationmentioning
confidence: 99%
“…To describe images, the semantic information is used to abstract the images into the form of topological graphs, which can simplify the preservation and comparison process of the environmental information of images. With prior knowledge of the map, the random walk algorithm [30,31] is used on the association graphs to match the semantic features and the scenes. Finally, the EPnP algorithm [32] is used to solve the UAV's position and pose for robust UAV relocalization and guarantee of UAV performing IoT tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Visual navigation methods can be categorized into two main categories: map-based [2,3] and map-less methods [4][5][6]. Some of them are based on teach and repeat techniques [4,5,[7][8][9][10]. They are considered as map-less methods.…”
Section: Introductionmentioning
confidence: 99%